Into the fire [compact disc, unabridged] : a firsthand account of the most extraordinary battle in the Afghan War - Meyer, Dakota, 1988- (Random House Audio, 2012)
In the fall of 2009, Taliban insurgents ambushed a patrol of Afghan soldiers and Marine advisors in a mountain village called Ganjigal. Firing from entrenched positions, the enemy was positioned to wipe out one hundred men who were pinned down and were repeatedly refused artillery support. Ordered to remain behind, Marine corporal Dakota Meyer disobeyed orders and rescued his comrades. Tells the story of the chaotic battle for the first time in a compelling way.